Faktor Risiko Penularan Malaria Vivak - Lina Handayani, Pebrorizal, Soeyoko (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Malaria in Indonesia is one of the important health cases, in particular outer part of Java-Bali. South Bengkulu Regency is one of the transmigration areas outer Java and Bali which is the endemic area toward malaria disease. From 34 communities’ health centers which exist, 19 community health centre are stated as the endemic are diseases in South Bengkulu Regency during last five years revealed the tendency of increasing the case annually. Up to now the eliminating of malaria in South Bengkulu Regency was emphasized on the medical aspect to cure the parasite and the management of vectors. Meanwhile the behavioral aspect had not got appropriate attention as well.Method and Result: This research was the observational by design of case control. The sample was gained from the Public Hospital Manna, Community Health Centre M.Thaha, and Community Health Centre Kedurang. It comprised from 36 cased and 72 controls. Data analysis was conducted descriptively by using table of frequencies distribution and analytically to know the relation between two variables by cross tabulation then was tested by using 2x2 table by Epi Info Program to know the amount of Odds Ratio (OR) and also see which variable having biggest risk to support the contamination of disease by using logistic linier. The data was analyzed by using SPSS version 10.0.Conclusion: Based on the result of this research, it could concluded that : 1) there was every significant relation between the distance of field to the house toward the incident of malaria (p=000) , 2) there was not present relation between the distance of rice field with the incident of malaria(p=0,133), 3) there was not present very significant relation between the habits to use mosquito net with the incident of malaria (p=0,000), 4) there was not present a relation between the usage of burnt mosquito poison with the incident of malaria (p=0,887), 5) there was not present significant relation between the habit to go outside in the night with the incident of malaria (p=0,002).Keywords: distance of the field, distance ofricefield, mosquito net, burnt mosquito poison, go outside in the night,malaria